The association between preterm births and assisted reproductive technologies - Stastna, Anna; Waldaufova, Eva; Fait, Tomas (Biomedical papers, 2024)
Aims. The aim of this study is to determine whether the risk of preterm births differs according to the conception method: with or without ART and according to the ART method used (in-vitro fertilisation (IVF) with fresh embryo transfer, frozen embryo transfer (FET) and oocyte receipt (OoR)).Methods. The research is based on individualised anonymised data on deliveries in Czechia in 2013-2018 (n=651,049) obtained from the National Health Information System. We employ the survival analysis approach applying survival functions (Life tables method) and Cox regression to model the risk of preterm births according to the conception method when controlling for a set of covariates.Results. The results revealed that the risk of preterm births in singleton pregnancies is higher for ART-treated women (1.56 to 2.06 depending on the ART method) than for non-ART-treated women. The proportion of preterm births differs according to the ART method; the highest proportion was observed for OoR mothers.Conclusions. Overall, the differences between ART-treated mothers according to the conception method are due mainly to the structural differences between mothers. When controlling for the covariates (Cox regression model), no significant differences were observed concerning the risk of preterm births for women who underwent fresh IVF, FET and OoR.
Keywords: preterm birth; assisted reproduction technology; in-vitro fertilisation; frozen embryo transfer; oocyte donation